Pulsed microwave assisted hot air drying of nutmeg mace for better colour retention - Mahendran, A Santhakumaran, J N Meetha, P Muhammadali, M I Joy, R (Journal of Spices and Aromatic Crops, 2016)
A study was conducted on application of novel drying technology for better color retention of mace. Pulsed microwave assisted hot air drying was investigated at three different power levels 0.5 kW, 1 kW and 1.445 kW with 30 seconds pulsation at a hot air temperature of 45°C and the color values of mace were compared with the market and fresh sample using colorimeter. Further, the major flavor compound, myristicin in mace was analysed.